An Explorative Study on the Effects of The Fourth Industrial Revolution on Employment in Small, Medium and Micro Enterprises - Jacobs, Gabriella (Department of Social Development, 2024)
The onset of the Fourth Industrial Revolution impacted most facets of life. As a services revolution, which was brought about by the merging of various sectors and phenomena such as nanotechnology, biotechnology, and Information Communication and technology systems, the Fourth Industrial Revolution will massively end, irreversibly altering the way that things are done, including in the SMMEs sector. Using the United Nations' Sustainable Development Goals numbers 8 and 9 and South Africa's National Development Plan as the guiding framework and legislation within which the Fourth Industrial Revolution will unfold in South Africa, this study, set out to carry out an exploitative case study of the fate of SMMEs by focusing mostly on automation and the fate of skilled and unskilled jobs. This study seeks to understand the experiences and perceptions of people working in SMMEs on the effects of automation on employment through their work experience in an SMME. It also seeks to determine the extent of the utilization, or lack thereof, of automation in the SMME sector. Other aims include an examination of the contingency plans to be put in place to prevent or minimise job losses. Overall, the study aims to identify whether the Fourth Industrial Revolution is having a negative or positive effect on employment in SMMEs. The methodology used was a mixture of literature review and key informant interviews conducted by business owners and workers in Small, Medium, and Micro Enterprises and also by experts in this sector. The main findings of this study were that without the prerequisite infrastructural development and the necessary digital literacy, South Africa's SMMEs will lose more jobs as a result of technological innovation and automation. This predicament will be exacerbated by the lack of reskilling and upskilling programmes meant to absorb those whose jobs would have been lost to automation. The conclusion reached was that the Fourth Industrial Revolution will not be useful in reducing unemployment, poverty, and inequality. On the contrary, it will widen these gaps and result in more unemployment and unemployability. Instead of being a beneficiary of the Fourth Industrial Revolution, the SMME sector will be one of the most affected sectors of the economy.